2021
DOI: 10.1088/2515-7655/abf41c
|View full text |Cite
|
Sign up to set email alerts
|

Chalcogenide perovskites for photovoltaics: current status and prospects

Abstract: Chalcogenide perovskite materials are anticipated to have favourable structural, optical and electronic characteristics for solar energy conversion, yet experimental verification of the numerous computational studies is still lacking. In this perspective we summarise and critically review the computational and synthetic achievements, whilst suggesting new pathways for achieving the goal of developing this exiting class of materials. Greater knowledge of phase chemistry would allow the realisation of bandgap en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 80 publications
1
29
0
3
Order By: Relevance
“…8,9 Recently, it has been proposed that ternary chalcogenides (TCs) with the general formula ABX 3 (where A and B are metals and X is S or Se), especially with the perovskite crystal structure, may be an appealing alternative, thanks to the electronic properties analogous to HOIPs, and a broad variety of possible chemical compositions that can be chosen to avoid the use of lead or other toxic metals. [10][11][12] It has also been shown that the experimentally prepared TCs exhibit good chemical properties and a high thermal stability. 9,[13][14][15][16] From the perspective of practical applications of TCs in optoelectronics, it is important to understand how they are affected by various thermodynamic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Recently, it has been proposed that ternary chalcogenides (TCs) with the general formula ABX 3 (where A and B are metals and X is S or Se), especially with the perovskite crystal structure, may be an appealing alternative, thanks to the electronic properties analogous to HOIPs, and a broad variety of possible chemical compositions that can be chosen to avoid the use of lead or other toxic metals. [10][11][12] It has also been shown that the experimentally prepared TCs exhibit good chemical properties and a high thermal stability. 9,[13][14][15][16] From the perspective of practical applications of TCs in optoelectronics, it is important to understand how they are affected by various thermodynamic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For concluding this section on inorganic HTMs, we highlight the last works exploiting 2D TMD HTMs [51,82] exceeding the 20% PCE threshold. 2D WS 2 was applied in p-i-n devices by Liu et al, [83] exploiting its ultrahigh hole mobility and its capability of driving high-quality epitaxial growth of the perovskite thin film, thus achieving about 21% PCE.…”
Section: Inorganic Htms For Pscsmentioning
confidence: 99%
“…As the chalcogenide counterparts of halide perovskites, chalcogenide perovskites (perovskites with oxygen, sulfur, or selenium as anions) can serve as promising alternatives consisting of nontoxic and abundant elements. Recently, Ruddlesden–Popper-type layered chalcogenide perovskites have been proved by experiments or predicated by theoretical calculations to have low band gaps and large optical absorption coefficients so that they could be potential next-generation sustainable semiconductor materials. For example, the graphene-like 2D Ca 3 Sn 2 S 7 chalcogenide perovskite (1L, 2L, and 3L) reported by Du et al.…”
Section: Introductionmentioning
confidence: 99%